Application of the NHT (Numbered Head Together) Learning Model to Improve Student Learning Outcomes at SDN 2 Sriwedari, Salaman, Magelang Regency for the 2020/2021 Academic Years - Utami, Uswatul Tri (Prosiding University Research Colloquium, 2021)
This study purpose to improve student learning outcomes by applying the NHT (Numbered Head Together) learning model with the research subjects of fifth grade students at Sriwedari 2 Elementary School, Salaman District, Magelang Regency. The research method used is CAR (Classroom Action Assessment) and the form of data collection is a multiple choice test. In the first cycle reached an average of 60.83. In the second cycle reached an average of 77.5. Based on this, it can be concluded that the NHT model can improve learning outcomes, so the NHT model can be used as an alternative after finding problems regarding student learning outcomes.